TRANSLATION ANALYSIS OF NEOLOGISMS IN THE LORD OF THE RINGS: THE FELLOWSHIP OF THE RING NOVEL - Nesya Tsurayya; Evert H. Hilman (IKIP Siliwangi, 2022)
The purpose of this research is to identify and examine the neologism classifications in J. R. R. Tolkien’s novel The Lords Of The Rings: The Fellowship Of The Ring, using Peter Newmark’s theory. The qualitative descriptive method with systematic approach is utilized here to generate data from a subjective perspective in collecting and analyzing both the English and Indonesian version of the novel. Molina and Albir’s translation techniques and other related theories are also applied in the research to support the analysis. From 59 out of 127 data, 8 (eight) classification of neologisms are found in the research which contain (1) transferred word (34%), (2) new coinages (19%), (3) eponym (12%), (4) new collocation (12%), (5) collocation with new sense (8%), (6) old word with new senses (7%), (7) derived word (5%), and (8) acronym (3%). Further, there are eight out of eighteen translation techniques applied in the research, they include Pure Borrowing (66%), Linguistic Amplification (8%) and Literal Translation (8%), Calque (7%), Established Equivalent (5%), and Adaptation (2%), Discursive Creation (2%), and Particularization (2%). Keywords: Neologisms, Translation Technique, Neologism Category